Developing Pop Up Book Learning Media On Theme 8 For First Grade In MI Islamiyah Pancakarya - Zaqiyatul Muna; Ma’as Shobirin; Ummu Jauharin Farda (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2022)
There are students who seem bored and drenched by the monotonous learning since they simply have to listen to the teacher's instruction, and there are even other students who are rushing about the classroom because the learning media employed by the teacher are not being utilized effectively. This research aims to develop the need for a pop-up media book for both teachers and students, as well as the validation of a pop-up media book on topic 8 for the first grade of Islamic elementary school MI Islamiyah Pancakarya Semarang. This approach to data collection research and development (R&D) research methodologies across the five stages of potential and problem, data collection, product design, design validation, and design revision. The data gathering methods include anglets, observations, interviews, and documentation, while the data processing methods include qualitative and quantitative analysis. This investigation resulted in a suitable media category for topic 8 of the first-grade MI Islamiyah Pancakarya Semarang thematic study. The overall harmonic character of the content is validated by the evaluation of 4.57 in the